Using think-aloud method in teaching reading skill - Syamsul Bahri Yusuf; Chairina Nasir; Chentenei Lapenia Ningsih Rohiman (Universitas Syiah Kuala, 2018)
There are many EFL students who still find learning English is difficult especially in comprehending the text passages being read. The Think Aloud Method is known to be one of the methods that are able to assist language learners in improving their EFL reading comprehension. The aim of this study was to find out whether students’ reading comprehension, particularly in identifying the main idea, supporting details, references, making inferences and interpreting vocabulary, improve after the implementation of this method in the teaching and learning process. The sample was the eighth grade students of a junior high school in Banda Aceh. This study employed a one group pre-test and post-test design. The findings showed that the mean score from the pre-test was 38 while from the post-test was 79. The critical value from t-table was 0.05, while the t-test level of significance was 1.71, so the t-test value was higher than the critical value of t-table (1.71 0.05). The reading aspects that improved most were detailed information, main idea and understanding inferences. The two other aspects, vocabulary and finding references also improved, but not as much as the other three aspects. Thus the hypothesis was accepted that the use of this method could significantly improve the students’ reading comprehension at the school under study, especially in comprehending meaning in a descriptive text. In conclusion, Think Aloud can be used to improve the ability of eighth grade students in EFL reading comprehension.